2018
DOI: 10.1038/s41418-018-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in neuronal metabolism contribute to the pathogenesis of prion disease

Abstract: Neurodegenerative conditions are characterised by a progressive loss of neurons, which is believed to be initiated by misfolded protein aggregations. During this time period, many physiological and metabolomic alterations and changes in gene expression contribute to the decline in neuronal function. However, these pathological effects have not been fully characterised. In this study, we utilised a metabolomic approach to investigate the metabolic changes occurring in the hippocampus and cortex of mice infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 86 publications
3
36
0
Order By: Relevance
“…(P=0.0039, control NBH vs RML mice, Student's t-test, Fig. 5a) providing evidence for enhanced oxidative stress as one hallmark of the disease and confirming previously reported increases in oxidative stress levels in prion-diseased mice [8]. Together with the enhanced levels of nitrergic stress associated with augmented expression levels of iNOS mRNA (Fig.…”
Section: Protein 3-nitrotyrosination Is Driven By Oxidative Stress Ansupporting
confidence: 88%
See 4 more Smart Citations
“…(P=0.0039, control NBH vs RML mice, Student's t-test, Fig. 5a) providing evidence for enhanced oxidative stress as one hallmark of the disease and confirming previously reported increases in oxidative stress levels in prion-diseased mice [8]. Together with the enhanced levels of nitrergic stress associated with augmented expression levels of iNOS mRNA (Fig.…”
Section: Protein 3-nitrotyrosination Is Driven By Oxidative Stress Ansupporting
confidence: 88%
“…We have previously shown that NBH mice lack any significant NADPH diaphorase signals at 10 w.p.i. [8]. This data illustrates a strong increase of NOS (NADPH activity) from 8 w.p.i.…”
Section: Prion Diseased Mice Show Signs Of Neuroinflammation Prior Tomentioning
confidence: 60%
See 3 more Smart Citations